Structure and microstructure of coronary dentin in non-erupted human deciduous incisor teeth - Costa Luciane R.R S.; Watanabe Ii-Sei; Kronka Márcia C.; Silva Marcelo C.P (Fundação Odontológica de Ribeirão Preto, 2002)
The dentin structure of non-erupted human deciduous mandibular and maxillary central and lateral incisor teeth was studied employing light and scanning electron microscopy. For light microscopy, nitric-acid-demineralized and ground sections were used. The sections were stained by hematoxylin-eosin, picrosirius and azo-carmim methods, and ground specimens were prepared using a carborundum disk mounted in a handpiece. For SEM study, teeth were frozen in liquid nitrogen and fractured at longitudinal and transversal directions. Structurally, demineralization and ground methods revealed tubules with primary and secondary curvatures, canaliculi, giant tubules, interglobular dentin, predentin, and intertubular dentin. Scanning electron microscopy showed three-dimensional aspects of dentinal tubules, canaliculi, peritubular dentin, intertubular dentin, and predentin. This study contributes to knowledge about dentin morphology showing characteristics of teeth not yet submitted to mastication stress.